Do modern family planning methods impact women’s quality of life? Jordanian women’s perspective - Alyahya, Mohammad S. (Health Qual Life Outcomes, 2019)
BACKGROUND: Although Jordan has made progress in meeting Family Planning (FP) needs in last decades, recently the use of FP methods has declined significantly. Women’s personal experiences, knowledge, and perceptions of how a FP method might impact their quality of life (QoL) can influence FP decisions. However, a lack of comprehensive understanding of the impact of modern FP methods on women’s QoL continues to exist among Jordanian couples. Therefore, this study aimed to investigate the relationship between the use of common modern FP methods and QoL among Jordanian women. METHODS: Using the WHOQOL-BREF questionnaire along with other questions, non-pregnant women of reproductive age were interviewed at their homes through face-to-face structured interviews. Women who visited the obstetrics and gynecology clinic of King Abdullah University Hospital for contraceptive advice and follow-up consultations were also included. RESULTS: A total of 548 women aged between 18 and 49 participated in the study. Based on the WHOQOL-BREF scale, the overall mean (SD) scores of the four domains were found to be average. Our findings show that women who used Intra Uterine Devices (IUDs) and women whose husbands used condoms had better QoL in the four domains (physical health, psychological health, social relationships, and environment) than those who used Oral Contraceptives (OCs). Women who used implant and injectable hormonal contraceptives had better QoL in terms of the physical health and social relationships domains. In contrast, women who had undergone permanent sterilization had lower QoL scores in all of the four domains. Further analysis revealed that women who had undergone tubal sterilization were less satisfied overall and more likely to experience side effects than women who used OCs. CONCLUSION: The choice to use contraceptives and decide freely whether and when to have children is regarded as a fundamental reproductive health right and is strongly linked to women’s health and QoL. Women who use OCs and women who have undergone permanent sterilization are likely to have lower QoL than women who use IUDs or implant and injectable hormones and those whose husbands use condoms.